2015
DOI: 10.3109/10428194.2014.941833
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation in patients with multiple myeloma receiving bortezomib-containing regimens followed by autologous stem cell transplant

Abstract: To investigate hepatitis B virus (HBV) reactivation and survival in patients with multiple myeloma (MM) receiving bortezomib-containing regimens, we analyzed 139 patients with MM receiving bortezomib-containing regimens in our hospital. Twenty-seven/139 patients were hepatitis B surface antigen positive (HBsAg+) with nine having DNA levels > 500 IU/mL, including four > 1000 IU/mL. All but five HBsAg+ patients were treated with lamivudine or entecavir before chemotherapy until at least 6 months after chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
2
25
2
1
Order By: Relevance
“…The additive immunosuppressive effect of bortezomib and autologous SCT in causing hepatitis B reactivation is an even more important question in the year 2015, since bortezomib-containing regimens in conjunction with autoSCT are now also being used to treat aggressive lymphomas in addition to myeloma. It is therefore urgent that further retrospective studies in other populations be undertaken to confirm the observations of Li et al [1]. Prospective studies are not possible, since the current standard of care for previously exposed patients mandates preventive antiviral treatment, which is highly successful if administered properly.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…The additive immunosuppressive effect of bortezomib and autologous SCT in causing hepatitis B reactivation is an even more important question in the year 2015, since bortezomib-containing regimens in conjunction with autoSCT are now also being used to treat aggressive lymphomas in addition to myeloma. It is therefore urgent that further retrospective studies in other populations be undertaken to confirm the observations of Li et al [1]. Prospective studies are not possible, since the current standard of care for previously exposed patients mandates preventive antiviral treatment, which is highly successful if administered properly.…”
mentioning
confidence: 89%
“…Bortezomib and autologous SCT are frequently used together in the treatment of myeloma, particularly during the last decade. In the study reported in this issue of Leukemia and Lymphoma, Li et al [1] suggest that autoSCT is associated with an increased risk of HBV reactivation particularly in patients who have previously received bortezomib-containing regimens.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Reactivation of HBV has been reported in patients treated for lymphoma, other haematological malignancies and in the setting of haematopoetic stem cell transplant [14,[19][20][21][22] . The prevalence of CHB in patients with lymphoma has been reported as high as 26% [15] .…”
Section: The Magnitude Of the Risk Of Hbvrmentioning
confidence: 99%